Adoption and impacts of agricultural technologies and sustainable natural resource management practices in fragile and conflict affected settings: A review and meta-analysis - Nshakira-Rukundo, Emmanuel; Tabe-Ojong, Martin Paul Jr.; Gebrekidan, Bisrat Haile; Agaba, Monica; Surendran-Padmaja, Subash; Dhebibi, Boubaker (International Food Policy Research Institute, 2023)
Climate change and conflicts co-exist in many countries with significant welfare and socio-environmental implications. Different approaches are being promoted to adapt and build resilience to these fragilities including the adoption of sustainable farm practices that have the potential to increase agricultural productivity and maintain environmental sustainability. We undertake a systematic review and perform a meta-analysis to understand and synthesize the adoption and impacts of agricultural technologies and natural resource management practices with a special attention to fragile and conflict affected settings. We employ state of the art machine learning methods to enable process and selection of appropriate papers from a universe of over 78,000 papers from leading academic databases. We find that studies on adoption and impact of agricultural technologies and natural resource management practices are highly clustered around Ethiopia and Nigeria. We do not find any studies on Small Island States. We observe a wide array of characteristics that influence adoption of these technologies. Of the over 1400 estimates of determinants collected, majority predict input technologies while very few studies and estimates are found in relation to risk management and mechanisation technologies. Our meta-analysis shows an average effect size of 7 - 9% for the different technologies and practices. For the outcomes: land productivity, food security and household welfare, we obtain effect sizes of 6, 8 and 9% respectively. We do not observe much in terms of publication bias. Both climate and conflict vulnerability not only cause far more food insecurity, poverty, and degradation of the environment on their own but also reinforce each other through the climate change – conflict linkage. For these detrimental effects to be curtailed, utilisation of climate-smart agricultural technologies and natural resource management practices need to be encouraged. We thus lend credence to the development, dissemination and upscaling of these sustainable practices. We observe a lot of space for growth and adoption of these technologies.